Phase‐Constrained Obligatory Late Adjunction. (18th November 2021) - Zyman, Erik
Abstract: It has sometimes been argued that adjuncts can merge late. This article provides a new argument for late adjunction and a new analysis of it. Exactly (or precisely ) can adjoin to a wh  phrase, and wh  movement can affect either the entire adjunction structure ( What exactly is it? ) or only the host ( What is it exactly ? ). Structures like what exactly can be generated VP internally, but surprisingly—and despite appearances— exactly cannot be stranded VP internally. The article argues that this can be understood if adjuncts merge late obligatorily, at the phase level: for H a phase head with complement XP, all adjunction within the HP phase must occur immediately before XP spellout. Further predictions of this analysis are shown to be correct. The larger picture that emerges is one in which the syntax prioritizes satisfying featural requirements: if so, it is not surprising that it waits until the last possible moment (within each phasal subderivation) to add in adjuncts.